Effect of Bioptron Light Therapy on post-menopausal low back pain: A randomized controlled study - Mohamed Abdelbaset Elemam Ahmed; Mohamed Ahmed Mohamed Awad; Abdel Hamid Abdel Aziz Atta Allah; Marwa Shafiek Mustafa Saleh; Shreen Rashad Aboelmagd (Universidad de Murcia, 2024)
Article accepted. The article will be published here soon. Pending final quality checks.